TYPHOID MARY - Yuldasheva Khusnora Khusinboy kizi (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract. This article explores the historical and medical significance of Mary Mallon—widely known as “Typhoid Mary”—as the first identified asymptomatic carrier of typhoid fever in the United States. It examines the implications of her case for modern public health policy, epidemiological surveillance, and the ethical tensions between individual liberties and collective safety. Drawing on primary historical records and contemporary analysis, the article reflects on how Typhoid Mary’s story influenced early 20th-century approaches to quarantine, disease control, and the evolving perception of carriers in infectious disease transmission.